Phase behavior of nematic-nanoparticle mixtures - Hölbl, Arbresha; Ranjkesh, Amid; Abina, Andreja; Kralj, Samo; Zidanšek, Aleksander (Frontiers in Soft Matter, 2023)
We study the effects of nanoparticles (NPs) on thermotropic nematic liquid crystals (LCs) in relatively dilute NP-LC mixtures. We are interested in the fundamental generic mechanisms that quantitatively and qualitatively affect the phase behavior of LC. A simple molecular field analysis shows that a phase transition is likely to occur upon entry into the ordered phase. Moreover, the interaction between nematogenic NPs and LCs could force a sergeant-soldier-like behavior in which only the phase behavior of one component is affected despite the symmetric appearance of the coupling term. When NPs are anisotropic, their influence on the LC phase behavior can be qualitatively different, depending on the anchoring, even in the absence of disorder. We illustrate numerically that a random-field- type disorder might impose either short-range, quasi-long-range or even long-range order might survive.